Twenty-five Years Excavating Flint Mines in France and Belgium: an Assessment - Bostyn, Françoise; Collet, Hélène; Ghesquière, Emmanuel; Hauzeur, Anne; Labriffe, Pierre-Arnaud de; Marcigny, Cyril; Lavachery, Philippe. Tł. (Archaeopress Archaeology, 2018)
Twenty-five years of experience in excavating flint mines allow us to give a methodological overview about sites characterized by the sheer depth of some structures, the often vast extensions of the deposits and the specialised activities that were carried out there. By comparing operations undertaken up to fifteen years apart, the importance of accurate stratigraphic and planimetric records becomes clear. Palaeoenvironmental approaches probably have to be multiplied in view of the results obtained when sampling is systematic. If the use of a mechanical excavator is inescapable to create large geological cross sections and allows the excavation of a large number of structures, an agreement emerges to consider that its exclusive use should be avoided. It should be regarded as a complement to be employed once a certain number of previous stages have been completed
il. ; 29 cm